2018
DOI: 10.1161/jaha.118.009833
|View full text |Cite
|
Sign up to set email alerts
|

Skin Autofluorescence–Indicated Advanced Glycation End Products as Predictors of Cardiovascular and All‐Cause Mortality in High‐Risk Subjects: A Systematic Review and Meta‐analysis

Abstract: BackgroundChronic deposits of advanced glycation end products produced by enzymatic glycation have been suggested as predictors of atherosclerotic‐related disorders. This study aimed to estimate the relationship between advanced glycation end products indicated by skin autofluorescence levels and the risk of cardiovascular and all‐cause mortality based on data from observational studies.Methods and ResultsWe systematically searched Medline, Embase, the Cochrane Central Register of Controlled Trials, the Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 54 publications
(82 reference statements)
6
28
0
Order By: Relevance
“…Improvements in both the quantitative and qualitative definitions of MetS agree with previous research, indicating that HbA1c is a good predictor of mortality and cardiovascular events [11]. Additionally, these findings are in line with previous evidence of a strong association between HbA1c and skin autofluorescence-indicated advanced glycation end-products (AGEs) [40], a tissue biomarker considered an indicator closely related with PWv, IMT and ACR [41], and associated with mortality and cardiovascular events [42].…”
Section: Discussionsupporting
confidence: 88%
“…Improvements in both the quantitative and qualitative definitions of MetS agree with previous research, indicating that HbA1c is a good predictor of mortality and cardiovascular events [11]. Additionally, these findings are in line with previous evidence of a strong association between HbA1c and skin autofluorescence-indicated advanced glycation end-products (AGEs) [40], a tissue biomarker considered an indicator closely related with PWv, IMT and ACR [41], and associated with mortality and cardiovascular events [42].…”
Section: Discussionsupporting
confidence: 88%
“…The deterioration of EC with AGE accumulation may, therefore, be the result of AGEs causing the functional decline of several organ systems that regulate EC, regardless of DM status. A recent meta-analysis demonstrated that SAF levels were a predictor of mortality in high-risk patients [15]. This could potentially be explained by the association between high SAF levels and reduced EC observed in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…Skin autofluorescence (SAF) has recently been developed as an accurate and noninvasive method to measure AGE accumulation in the skin. SAF has received attention as its results can provide a useful predictor of allcause mortality and cardiovascular mortality in patients who are high-risk [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, MI rat model established in this study was characterized by increased amount of VAs. MACE was reported to be closely associated with AGEs content in high-risk patients with atherosclerotic cardiovascular diseases [24]. In the present study, our cohort analysis suggested that post-MI PVCs were more frequent in STEMI patients complicated with diabetes.…”
Section: Discussionsupporting
confidence: 56%